Combined probiotics attenuate chronic unpredictable mild stress-induced depressive-like and anxiety-like behaviors in rats - Huang, Li; Lv, Xia; Ze, Xiaolei; Ma, Zewei; Zhang, Xuguang; He, Ruikun; Fan, Junting; Zhang, Meilin; Sun, Boran; Wang, Fang; Liu, Huan (Frontiers in Psychiatry, 2022)
Increasing evidence indicated that probiotics can be effective in improving behaviors similar to depression and anxiety disorders. However, the underlying mechanisms remain unclear, as is the effects of single vs. combined probiotics on depression and anxiety. This study aimed to determine whether combined probiotics could attenuate depressive-like and anxiety-like behavior induced by chronic unpredictable mild stress (CUMS) and its potential mechanisms. Rats underwent CUMS treatment and then administered Lactobacillus rhamnosus HN001 (HN001) or Bifidobacterium animalis subsp. lactis HN019 (HN019), alone or in combination. Levels of neurotransmitters, inflammatory factors, and the gut microbiota were measured. HN001 and (or) HN019 treatment improved depressive-like and anxiety-like behavior in rats, including increased moving distance and exploratory behavior (p < 0.05). In addition, altered gut microbiota structure induced by CUMS was amended by HN001 and/or HN019 (p < 0.05). HN001 and/or HN019 intervention also remarkably normalized levels of 5-HT, DA, NE, HVA, DOPAC, HIAA, TNF-α, IL-6, IL-18 and IL-1β in CUMS rats (p < 0.05). Furthermore, the effects of combined probiotics on decreasing inflammation and improved gut microbiota (Chao1 index and ACE index, p < 0.05) were superior to the single probiotics. Moreover, spearman analysis showed a certain correlation between the different microbiota, such as Firmicutes, Bacteroidetes, Verrucomicrobias, Proteobacterias and Actinobacterias, and inflammation and neurotransmitters. These findings suggested that CUMS induced depressive and anxiety-like behaviors can be alleviated by the combination of probiotics, which was possibly associated with the alterations in the gut microbiota composition and increased neurotransmitters and decreased inflammatory factors.